RUMAH MASYARAKAT PESISIR PANTAI DI KAWASAN PERMUKIMAN DESA LAGASA PASCA REKLAMASI PANTAI âDengan Tinjauan Khusus Unsur-Unsur Arsitektur Yang Dipertahankanâ Kasus: Dusun Wabhahara Desa Lagasa Kecamatan Duruka Kabupaten Muna Provinsi Sulawesi Tenggara - , LA NGKURI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The present of beach reclamation at settlement area of Lagasa Village constitutes one of government effort to arrange and live irregular settlement condition in the place, so it can create settlement environment balance which is arranged well and orderly, and give fresh life condition in the area. Therefore, now days the society in the place have good development of economy, social, and its housing forms. But, the concept of society tradition from old generation that can not be separated from sea life in designing their house still kept or it is not balanced with the development. It is seen from architecture view toward architecture element indications that is still kept in the society housing at the Lagasa village after reclamation beach. The focused problem in this study is âDefended Architecture Elements on House at the Lagasa Village Settlement after Beach Reclamationâ. Based on the problem, the study questions are: (1) what are architecture elements defended on society house at Lagasa village after beach reclamation? And (2) what are the factors that influence the defended architecture elements? The expected significant of this study is as local culture inventory at Muna regency and it can be used for further studies of defended architecture elements on sea area. Besides, the result of this study can be used as policy determiner in developing sea area settlement, in order to consider its internal society capacity (community based development). Thus, when making planning and designing sea area settlement, it can help its society mobility development, and look after suitable traditional architecture values with coast society. This study uses qualitative method based on rational paradigm with taking sample of whole houses that is not lose and still kept of its area, and it is not separated from local value system, however in taking sample still done by purposive sampling, namely just several houses that represent from all house in the settlement area. The data collected by using observation of field direct observation, measuring, arranging, documentation, and interviewing. The result of this study shows that concept of society house development at Lagasa village can not be separated from society tie to its ancestors as settler in the sea area. In the implementation, it covers defended architecture elements on coast society house of settlement location, settlement orientation, house base form, and house building technique. This tie concept have life value rule as sailor, physic rule as house identity, and adaptation to settlement environment, and religious ceremony activity done by society at the coast of Lagasa village. The concept based on or influenced by society tie the sea, society belief system, social and family relationship, job, knowledge, and natural environment at the settlement area of Lagasa village.